Fenomena social loafing pada mahasiswa dalam pengerjaan tugas kelompok - Mustofa, Muhammad Royhan (Maliki Interdisciplinary Journal, 2025)
The phenomenon of social loafing refers to the tendency of students to reduce their effort when working in groups. In group assignments, unequal role distribution often occurs, with some members bearing heavier responsibilities while others contribute minimally. This condition may decrease teamwork effectiveness, hinder academic achievement, and trigger conflicts among members. Social loafing is influenced by various factors such as motivation, responsibility, learning systems, and interpersonal dynamics. Its impact is not only seen in the quality of academic results but also in the development of students’ social skills. Therefore, understanding the phenomenon of social loafing among university students is crucial to designing effective prevention strategies that support collaborative learning in higher education.